Protective role of nitric oxide on nitrogen-thiol metabolism and amino acids profiling during arsenic exposure in Oryza sativa L - Praveen, Afsana (Ecotoxicology (London, England), 2020)
Nitric oxide (NO) being a signaling molecule inside the plant cells, play significant role in signaling cascades and protection against environmental stresses. However, the protective role of NO in alleviating As toxicity in rice plants is currently not available. In the present study, the level of NO, nitrogen (N), inorganic N (nitrate, ammonium), thiols {TT (Total thiols), NPT (Nonprotein thiol)} and AAs contents along with N assimilating enzymes (NR, GDH, GOGAT) were analyzed after exposure of AsIII/NO treatment alone, and in combination. NO supplementation enhanced the content of N, inorganic N & thiol contents, NR, GOGAT activities, when compared with AsIII exposure alone. In AsIII exposed rice seedlings, content of AAs (except His, Arg, Met) reduced over the control, while supplementation of SNP improved AAs contents, compared to AsIII treatment alone. In conclusion, rice seedlings supplemented with NO tolerate the AsIII toxicity by reducing the N related parameters, thiol contents, altering the AA profile and enhanced the nutritional quality by increasing EAAs (essential amino acids) and NEAAs (non-essential amino acids)